2000
DOI: 10.1086/315752
|View full text |Cite
|
Sign up to set email alerts
|

Host Specificity of Vancomycin‐ResistantEnterococcus faecium

Abstract: Amplified-fragment length polymorphism (AFLP) analysis was used to investigate the genetic relationships among 255 vancomycin-resistant Enterococcus faecium (VREF) strains isolated from hospitalized patients, nonhospitalized persons, and various animal sources. Four major AFLP genogroups (A-D) were discriminated. The strains of each taxon shared >/=65% of the restriction fragments. Most isolates recovered from nonhospitalized persons (75%) were grouped together with all pig isolates in genogroup A. Most isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
161
2
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(195 citation statements)
references
References 62 publications
(68 reference statements)
24
161
2
4
Order By: Relevance
“…Although previous molecular epidemiologic studies on limited numbers of strains suggested host specificity and overrepresentation of certain clones in hospital outbreaks (14,15), these studies did not elucidate the patterns of evolutionary descent among VRE. We determined the population structure of 411 VRE and vancomycin-susceptible E. faecium (VSE) isolates by using multilocus sequence typing (MLST), explored the evolutionary origin of epidemic isolates associated with documented hospital outbreaks and other isolates, and assessed the association with ampicillin resistance and the presence of a recently discovered putative pathogenicity island (PAI) in E. faecium (16).…”
mentioning
confidence: 85%
“…Although previous molecular epidemiologic studies on limited numbers of strains suggested host specificity and overrepresentation of certain clones in hospital outbreaks (14,15), these studies did not elucidate the patterns of evolutionary descent among VRE. We determined the population structure of 411 VRE and vancomycin-susceptible E. faecium (VSE) isolates by using multilocus sequence typing (MLST), explored the evolutionary origin of epidemic isolates associated with documented hospital outbreaks and other isolates, and assessed the association with ampicillin resistance and the presence of a recently discovered putative pathogenicity island (PAI) in E. faecium (16).…”
mentioning
confidence: 85%
“…Using molecular typing, it was shown that outbreak strains isolated from hospitalized patients are genetically different from VREF strains present in the fecal flora of nonhospitalized individuals (29). Interestingly, strains recovered from nonhospitalized persons are genetically related to pig isolates (29).…”
mentioning
confidence: 99%
“…To our knowledge, type I in this study likely corresponds to type B of the European isolates reported by Willems et al (20), except for the IS1542 insertion. Type II corresponds to type E. In particular, type IIc appears to be identical to subtype E13 (14,20). All types of the Tn1546-like elements in this study harbored IS1542, which is restricted to Europe, mainly the United Kingdom.…”
Section: Vol 42 2004mentioning
confidence: 63%
“…Until recently, IS1216V, IS1542, IS1251, and IS1476 were reported in VanA VRE. IS1216V is known to be ubiquitous in vanA elements (9,20), whereas the other three IS elements appear to be geographically restricted. For example, IS1542 is frequently found in clinical and poultry VRE isolates from the United Kingdom and Ireland (14,22).…”
Section: Vol 42 2004mentioning
confidence: 99%
See 1 more Smart Citation